Animal Medicine in Medical Practice in Batak Toba Tribe - Vicky Rifai Adriansyah,; Sri Alem Br Sembiring,; Rutmika L Simanullang,; Hagata Fikasani,; Desi Melince Purba,; Rachel Meilisa Angelina Nadeak,; Bella Selvia Hutabarat,; Wahyu Kurniawan, (Indonesian Journal of Medical Anthropology, 2023)
This article explains how traditional medicine, especially those that use animals in traditional medicine facilities of the Batak tribe, Animal medicine is a medical practice carried out by means of animals as mediators or as herbs for consumption in curing infectious diseases. Diseases that can be cured by the use of this animal also vary from naturalistic diseases such as typhus, toothache, and ulcers to diseases such as gadam. This paper focuses on the Toba Batak tribe with data collection techniques in the form of primary data in the form of interviews and also through direct experience of the author and secondary data in the form of literature reviews by reviewing written writings from online databases. Research was conducted on Batak people and the slap animals that are often used for treatment. From the results of research, it is known that, until now, these treatment activities still exist despite modern medicine.